Prácticas y significados: la Campaña de Alfabetización de Adultos, 1944-1950 (Estudios) - Auqui Calle, Freddy Orlando (2023)
This paper studies the Adult Literacy Campaign led by the National Union of Journalists (UNP) and the League for the Education of Illiterates (LEA Group), between 1944 and 1950. It examines the campaign as part of the culturalization and citizen-building processes in the 1940s. Reading, writing, notions of calculus, civic practices, and Spanish as the national language were among the skills and values promoted by the campaign in its courses. This knowledge was intended to create a new, civilized individual worthy of being incorporated into the nation and the political community of citizens.